Electromagnetic processes in the magnetic-pulse straightening tool - inductor system with an azimuth gap - Gnatov, A.; Argun, Sch.; Ulyanets, O.; Гнатов, А. В.; Аргун, Щ. В.; Ульянец, О. А. (Харківський національний автомобільно-дорожній університет, 2016)
Investigations of the spatial distribution of the eddy currents are excited by field of flat circular single-turn inductor system with nonmagnetic perfectly conducting metal objects were carried out. We constructed volumetric epures of the amplitude-spatial distribution of total current density where the total current was induced. The obtained correlations of the radial distribution of induced current azimuthal component and the azimuthal distribution of induced current radial component were compared with the calculation data. It is proved that violation of the single-turn inductor system axial symmetry gives rise to the induced current radial comp component.
Електромагнітні процеси в інструменті магнітноімпульсного рихтування – індукторна система с азимутальним розрізом
Электромагнитные процессы в инструменте магнитно-импульсной рихтовки – индукторная система с азимутальным разрезом
Keywords: straightening; induction system; electromagnetic processes; рихтовка.; індукторна система; електромагнітні процеси; индукторная система; электромагнитные процессы; 621.318.4